HUBUNGAN PENGENDALIAN NYERI ( PAIN CONTROL ) DENGAN INTENSITAS NYERI PADA PASIEN KANKER DI RSUD DELI SERDANG LUBUK PAKAM TAHUN 2018 - Herri Novita Tarigan; Astuti Sari (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2018)
Cancer is an abnormal cell growth which tend to be attack the surrounding tissue and spread to other organs which is far away. The cause of cancer is uncontrolled cell proliferation. Whereas the complaints that often appear on patients with cancer is pain. Cancer pain is one result of the most feared cancer patients. In fact, pain is the most recent cancer symptom. When according to the intensity that the patient feel subjectively. This research aimed to analyzed the relationship between pain control with pain intensity on cancer patients. With descriptive correlation research design. Data collection started from February to April 2018. With the number of 96 respondents by using total samplingas the research instrument that used as method of sample collecting, demographic data, pain control questionnaires and observation sheets. The result of the research showed that the sign value is 0,005 which showed the correlation between pain control score with pain intensity is significant correlation value is -0,284. With a negative direction. Wherees the better of pain control means the lower of pain intensity. The correlation between pain control with pain intensity is two way relationship. Suggestion : Hopefully this research can be useful in the future in controlling of pain cancer patients.